ROLE OF LAW ENFORCEMENT ACTIVITIES IN THE FISHERIES RESOURCE MANAGEMENT - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 1999)
Enforcement activities is important to determine the success of fisheries management. However, enforcement is costly for Indonesia which made up from many islands and has very long coastline. Therefore, it is needed to find the alternative with least in cost. One of the feasible alternatives is by empowering fishers and their communities to monitor and surveillance the fisheries resources in their adjacent. This system is rather using traditional concept of community-based or co-management.